2022
DOI: 10.1155/2022/4568145
|View full text |Cite
|
Sign up to set email alerts
|

Association between Genetic Polymorphisms in Methylenetetrahydrofolate Reductase and Risk of Autoimmune Diseases: A Systematic Review and Meta-Analysis

Abstract: Methylenetetrahydrofolate reductase (MTHFR) is a critical rate-limiting enzyme in the homocysteine/methionine metabolism pathway that is implicated in the pathogenesis and progression of autoimmune diseases. Previous association studies have been performed to investigate the effect of polymorphisms in MTHFR on the risk of autoimmune diseases with inconsistent results. Therefore, this meta-analysis was designed to assess the association between the MTHFR 677 C/T and 1298 A/C polymorphisms and the susceptibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The growing recognition of differential methylation of DNA in the pathogenesis of autoimmune disease [121,122,123] and the linkage between autoimmune disease and elevated Hcy [124,125] raises the specter of increased autoimmune disease in those with MTHFR (methylenetetrahydrofolate reductase) variants afflicted with LC. Indeed a recent meta analysis demonstrated a direct connection between MTHFR 677 C/T and 1298 A/C polymorphisms and increased risk of autoimmune disease [126]. According to the CDC, more than half of Americans have at least one MTHFR polymorphism.…”
Section: Magnesium and B Vitaminsmentioning
confidence: 99%
“…The growing recognition of differential methylation of DNA in the pathogenesis of autoimmune disease [121,122,123] and the linkage between autoimmune disease and elevated Hcy [124,125] raises the specter of increased autoimmune disease in those with MTHFR (methylenetetrahydrofolate reductase) variants afflicted with LC. Indeed a recent meta analysis demonstrated a direct connection between MTHFR 677 C/T and 1298 A/C polymorphisms and increased risk of autoimmune disease [126]. According to the CDC, more than half of Americans have at least one MTHFR polymorphism.…”
Section: Magnesium and B Vitaminsmentioning
confidence: 99%
“…The results of the literature research revealed that IL-1A rs2856836 and rs3783550 ( 66 , 67 ), IL-10 rs1800871 ( 68 , 69 ), IL-12B rs17860508 ( 70 , 71 ), protein tyrosine phosphatase non-receptor type 22 ( PTPN22 ) rs2476601 ( 16 , 72 ), cyclooxygenase ( COX )-2 and ( PTGS )-2 rs20417 ( 73 75 ), CYP17A1 rs743572 ( 76 , 77 ), STAT4 rs7574865 ( 78 , 79 ), Toll like receptor 4 ( TLR4 ) rs4986791 ( 76 , 80 ) and methylenetetrahydrofolate reductase ( MTHFR ) rs1801133 ( 81 83 ) SNPs are associated with both diseases under investigation ( Table I ). The common genetic targets and their corresponding genes have been further analyzed towards estimating the candidate gene regulatory network and the major categories of the biological pathways using the GeneMANIA and the Reactome Knowledgebase platforms, respectively ( Fig.…”
Section: Shared Susceptibility Loci Between As and Endometriosismentioning
confidence: 99%
“…The 5,10-methylenetetrahydrofolate reductase ( MTHFR ) gene is located in chromosome 1p36.3, encoding a key rate-limiting, regulatory enzyme in folate and homocysteine metabolism, which catalyzes the conversion of 5,10-methylenetetrahydrofolate to 5-methyltetrahydrofolate ( 131 ). The MTHFR rs1801133 (Ala222Val) SNP, which is located in exon 4, has been found to be significantly associated with both AS and endometriosis ( 81 83 ). It has been previously suggested that polymorphisms in the MTHFR gene may result in alterations in gene expression levels and protein function, thus leading to an abnormal metabolism of 5,10-methylenetetrahydrofolate ( 82 , 83 ).…”
Section: Shared Genetic Polymorphisms and Biological Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing recognition of differential methylation of DNA and RNA in the pathogenesis of autoimmune disease [116][117][118] and the linkage between autoimmune disease and elevated Hcy [119,120] raises the specter of increased autoimmune disease in those with MTHFR (methylenetetrahydrofolate reductase) variants afflicted with LC. Indeed a recent meta analysis demonstrated a direct connection between MTHFR 677 C/T and 1298 A/C polymorphisms and increased risk of autoimmune disease [121]. According to the CDC, more than half of Americans have at least one MTHFR polymorphism.…”
Section: Magnesium and B Vitaminsmentioning
confidence: 99%